Pendidikan Islam Transformatif Dalam Perspektif Psikologi Merdeka Belajar - Siti Ria Farhaeni; Gazi; Era Mutiara Pratiwi; Ismail; Fathurrahman Muhtar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the concept of transformative Islamic education, examine the psychological aspects of the Merdeka Belajar concept, and analyze the relevance of transformative Islamic education from the psychological perspective of Merdeka Belajar. This study uses a qualitative approach with library research. Data sources were obtained from various scientific journals, books, and articles relevant to transformative Islamic education, educational psychology, humanism, and Merdeka Belajar. Data collection techniques were conducted through documentation studies, while data analysis used the Miles, Huberman, and Saldaña model, which includes data condensation, data presentation, and conclusion drawing. Data validity was carried out through source triangulation. The results show that transformative Islamic education is an educational paradigm that emphasizes the holistic development of students through the integration of intellectual, spiritual, moral, emotional, and social aspects. Meanwhile, the psychological aspects of Merdeka Belajar emphasize humanistic, constructivist, and progressivist approaches oriented towards active learning, learning freedom, creativity, critical thinking, and student-centered learning. The analysis also shows that transformative Islamic education has a strong relevance to the psychology of Merdeka Belajar (Freedom to Learn) because both emphasize humanistic learning, character development, self-actualization, and the formation of independent, critical, creative, and morally upright students.